PENGARUH ADIKSI INTERNET TERHADAP PROKRASTINASI AKADEMIK PADA SISWA SMPN 1 CUGENANG SELAMA MASA PANDEMI COVID-19 - Hartini Nur Sholihah; Nahda Kurnia Juniati; Pradiptya Septiyanti Putri (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2022)
During the pandemic, it was found that there was an increase in internet use among students, internet use became uncontrollable, and had the potential to become internet addiction. Students cannot regulate their internet usage which ultimately affects their routine as students, students tend to delay their academic assignments or known as academic procrastination. This study aims to determine how the influence of internet addiction on academic procrastination of SMPN 1 Cugenang students during the covid-19 pandemic. This study uses a quantitative method which was conducted on a population of 75 students. In this study, internet addiction was measured using the internet addiction test (IAT), which was adapted in Indonesian by dr. Rakhmad and the measuring instrument for academic procrastination were made by Aminah (2020) based on the theory of Ferrari et al (1995). To analyze the data, the researcher used a regression test with the help of SPSS 25. From the results of this study, it was found that there was a significant influence between internet addiction on academic procrastination of SMPN 1 Cugenang students, with an influence value of 12.4%. This means that the more severe the student's internet addiction, the higher the level of academic procrastination.